-8x+3=11x+6

Simple and best practice solution for -8x+3=11x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8x+3=11x+6 equation:


Simplifying
-8x + 3 = 11x + 6

Reorder the terms:
3 + -8x = 11x + 6

Reorder the terms:
3 + -8x = 6 + 11x

Solving
3 + -8x = 6 + 11x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11x' to each side of the equation.
3 + -8x + -11x = 6 + 11x + -11x

Combine like terms: -8x + -11x = -19x
3 + -19x = 6 + 11x + -11x

Combine like terms: 11x + -11x = 0
3 + -19x = 6 + 0
3 + -19x = 6

Add '-3' to each side of the equation.
3 + -3 + -19x = 6 + -3

Combine like terms: 3 + -3 = 0
0 + -19x = 6 + -3
-19x = 6 + -3

Combine like terms: 6 + -3 = 3
-19x = 3

Divide each side by '-19'.
x = -0.1578947368

Simplifying
x = -0.1578947368

See similar equations:

| 4n+13=n-i | | 9x-3(x-5)=6x+3 | | -2m=-(n-8) | | f-4=-12 | | x+.5=2.5 | | 3+x-10+4x=28 | | -56.4+b-48.11=71.3 | | 2(4x+8)=48 | | 3x-6=5x+27-2x | | -11=b+3 | | s-8=18 | | 3(6+x)-7=-1+5x | | -6=(y/5)+4 | | 0.5a-3=0.3(2a-3) | | -35.5=r+(26.3) | | 7x-10=2x-35 | | 4(x+5)=44 | | -1(x-10)=7 | | 3-2n=17 | | -1(x-10)=10 | | x+(-23.9)=-1 | | 6(2n+3)-2n=28 | | 18-(5m+5)=5+3m-16 | | -2p+7=5-(7p+7) | | -15=y-26 | | -(-6r+1)=-(9+6r)+8r | | 18+-7=-1+2x | | 6y-12=-24+2x | | 9(3x+4)-3x=4(6x+8) | | 3*(4+x)=28+x | | 7(5a-4)-1=14-18a | | 30+2y=32 |

Equations solver categories